1989
DOI: 10.1080/02791072.1989.10472161
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bromocriptine for the Treatment of Attention Deficit Disorder in Two Chemically Dependendent Patients

Abstract: The dually diagnosed patient with attention deficit disorder, residual type (ADD-RT) may be especially prone to cocaine abuse, because ADD includes dopamine deficiencies and cocaine is a dopamine agonist. It is hypothesized that bromocriptine, a dopamine agonist, will reduce a patient's craving for cocaine and simultaneously address the patient's ADD-RT symptoms. A single-organism, double-blind research design is used to evaluate the efficacy of bromocriptine, as measured by scale 9 of the MMPI, the digit span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the mid‐1980s, a not inconsiderable number of case reports were published on the treatment of adult ADHD in patients with SUD (primarily cocaine dependence, although a few cases of alcohol dependence were also reported) treated with pemoline or bromocriptine . Later, various open studies reported positive findings (see Table ) regarding the clinical utility of several different drugs (stimulants and some non‐stimulants) in patients with this dual disorder.…”
Section: Should Adult Adhd Be Treated Pharmacologically In the Contexmentioning
confidence: 99%
“…In the mid‐1980s, a not inconsiderable number of case reports were published on the treatment of adult ADHD in patients with SUD (primarily cocaine dependence, although a few cases of alcohol dependence were also reported) treated with pemoline or bromocriptine . Later, various open studies reported positive findings (see Table ) regarding the clinical utility of several different drugs (stimulants and some non‐stimulants) in patients with this dual disorder.…”
Section: Should Adult Adhd Be Treated Pharmacologically In the Contexmentioning
confidence: 99%
“…15 Consequently, it has been suggested that ADHD symptoms might represent a particular vulnerability to substance abuse and, thus, that it is important to treat these symptoms in order to increase the addicted individual's likelihood of obtaining abstinence. 17,18 These theoretical rationales have given rise to several evaluations of MPD's effectiveness in treating cocaine dependent patients with ADHD. These evaluations, which include case report studies and a small pilot study, suggest that MPD is a promising treatment for these comorbidly-diagnosed individuals.…”
Section: Introductionmentioning
confidence: 99%